**Converse: Q => P**

The converse of P=>Q is Q=>P

The Premise(P) and the Conclusion(Q) switch places. The Conclusion becomes the Premise, the Premise becomes the Conclusion.

**Inverse: ****not P => not Q
**

The inverse of P=>Q is (not P => not Q)

Negate both the Premise(P) and the Conclusion(Q)

**Contrapositive: not Q => not P**

The Contrapositive of P=>Q is (not Q => not P)

Contrapositive a combination of the converse and the inverse. To get the Contrapositive just Negate and switch The Premise(P) and The Conclusion(Q).

**Example**

P = The Traffic Light is Green

Q = The Car Drives over the crossing

P => Q is then:

If the I fall into the lake, then I get wet.

The Contratpositive of P => Q is then: not Q => not P is then:

If I am not wet, then I did not fall into the lake.